Քաղաքական գործընթացներն Արցախում (1986–1991 թթ.) - Հակոբյան, Տարոն (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Սույն հոդվածում ներկայացվում են 1986–1991 թթ. Արցախում տեղի ունեցած քաղաքական գործընթացները՝ հատկապես կարևորվել են Արցախյան շարժման նոր փուլի համատեքստում ստեղծված ընդհատակյա և ոչ ընդհատակյա կազմակերպությունների դերն ու նշանակությունը: Իրադարձությունների վերլուծությունը ցույց տվեց, որ շարժման նոր փուլը զարթոնք ապրեց ազգային նկարագիր ունեցող երիտասարդության և մտավորականության ջանքերի շնորհիվ: Հետագայում շարժման մեջ ձևավորվեց երկու հակառակ քաղաքական ուղղություն, որոնց պայքարը իր բացասական ազդեցությունը թողեց ազատագրական պայքարի որակի վրա: Քաղաքական պայքարի փոփոխության արդյունքում փորձ կատարվեց համախմբել քաղաքական ուժերին, սակայն Լեռնային Ղարաբաղի (Արցախի) Հանրապետության (ԼՂՀ) հռչակումից հետո տեղի ունեցած քաղաքական գործընթացները ապացուցեցին հակառակը: Ներքաղաքական խմորումները ավելի ակնհայտ դարձան 1992 թ. հունվարի 6–7-ը ԼՂՀ առաջին գումարման Գերագույն խորհրդի (ԳԽ) նախագահի ընտրությունների ժամանակ, երբ բացահայտ երևաց երկու հակոտնյա քաղաքական ուժերի պայքարը: Իշխանության եկած ուժերին հաջողվեց պահպանել ներքաղաքական կայունությունը, դրսևորել քաղաքական կամք, որի արդյունքում երկիրը ժամանակավորապես դուրս եկավ ստեղծված իրավիճակից: The article presents the political events in Artsakh in 1986-1991. Special attention is paid to the role and significance of the underground and nonunderground organizations created in the context of the new stage of the Artsakh movement. Throughout the 70 years of the existence of the USSR, violence and persecution were practiced against the Armenian population of Artsakh. Despite this, the struggle for joining Mother Armenia never ceased. Individual episodes of this persistent struggle, which for decades took the form of statements, petitions, and unrest in Soviet Armenia and the NKAO, were silenced or suppressed by the high-ranking Soviet leadership. The relatively favorable political conditions created in the USSR after 1985 provided the Armenian population of Artsakh with the opportunity to once again defend their violated rights and demand the unification of the Nagorno- Karabakh Autonomous Oblast with the Armenian Soviet Socialist Republic. Initially, the leadership of the movement tried at every opportunity to present the struggle of the Artsakh people in Moscow in the light of the ideas of reconstruction and glasnost in order to give it a legal appearance. However, ignoring the right of the Armenian population of Artsakh to self-determination and the legal and political justification of its demands, Azerbaijan, under the aegis of Moscow, once again preferred uncivilised methods of resolving the issue, or, more precisely, its extermination by organizing ethnic cleansing. The movement was born in the whirlwind of national awakening. At first it was led by intellectuals with a national mindset and young people imbued with a national ideology. Later, it was joined by active members of the Communist Party, as well as heads of institutions and enterprises who attempted to lead the movement. Later on, two opposing political currents were formed in the movement, whose activities had a negative impact on the liberation struggle. As a result of the change in the format of the struggle, an attempt was made to unite political forces. The political processes after the proclamation of the Nagorno-Karabakh Republic (Artsakh) proved otherwise. The internal political turmoil became more obvious during the elections of the Chairman of the NKR Supreme Council of the first convocation on 6-7 January 1992, when the conflict between the opposing forces was quite aggressive. The forces that came to power managed to preserve internal political stability, showed political will, as a result of which the country temporarily got out of the situation. Thus, by overcoming obstacles, bypassing political and military conflicts, the forces involved in the liberation struggle, thanks to their determination, were able to move in accordance with the requirements of the time, while bearing the burden of organizing the liberation struggle.
Keywords: Պատմություն